Implementasi Kontrol PID pada Kopel Motor DC dengan Menggunakan Filter Kalman - Salima Nurrahma; Tegar Arif Berbudi; Muhammad Rakha Firdaus; Galang Izzaulhaq; Imroatul Hudati (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2023)
This paper describes a DC motor clutch system that uses  control methods PID and uses a Kalman filter. The methods used aim to obtain stable results from the DC motor coupling system used. To get the appropriate results, several stages were carried out such as hardware design where this process was carried out by pairing all the components used including the power supply, DC motor driver, Arduino Uno, potentiometer and the two coupled DC motors. This system uses an input voltage of 12 V and will then be processed by the motor driver to drive the DC motor. Based on the results that have been obtained and the system response after being given control. It can be observed that when the system uses the Kalman filter and uses the PI control the system response results have a small steady state error.